Investigating Computational Solutions for Metadata Processing in Software Engineering Experiments - Santana, Filipe A.; Cordeiro, André F. R.; OliveiraJr, Edson (Anais da Escola Regional de Engenharia de Software (ERES); 2024: Anais da VIII Escola Regional de Engenharia de SoftwareDO - 10.5753/eres.2024.4283, 2024)
Metadata consists of elements that describe specific data content. When structured according to standards, metadata improves data interoperability. In this context, it is understood that adopting metadata could contribute to describing experiments in Software Engineering. Furthermore, the use of tools can help in the management. Considering the context, this study includes a Systematic Mapping to identify solutions for the computational processing of metadata in SE experiments. Following the execution of the search strategy, a total of 31 studies were reviewed. The mapping did not achieve satisfactory results. Consequently, a Non-Systematic Review was conducted. In this case, a set of solutions were found.